A Network Analysis of Domestic Violence Beliefs Among Young Adults in India - Rodriguez, Ana L. (Journal of interpersonal violence, 2021)
This study sought to describe the system of beliefs on gender, attitudes toward women, and wife beating, in young adults who live in Mysore, India. Furthermore, it identified structural sex differences in the interplay of values among these matters that can affect individual and community views toward domestic violence. Drawing from survey data gathered from 265 young adult Indian men and women, this study used network analysis to graph a correlation network of beliefs and attitudes toward domestic violence. Node, scale, and network structure descriptions allowed for comparisons among male and female participant responses. The findings support the assertion that there are sex differences among the system of beliefs toward wife beating among Indian young adults. Gender ideology, masculine role in relationships, and legal and social consequences of wife beating emerged as the most important values to focus on when addressing young men’s beliefs of domestic violence and attitudes toward women. In contrast, values influencing women’s perceptions of domestic violence are more complex and related to multiple beliefs about women’s power, family structure, and social and legal implications of domestic violence. The results highlight the importance of recognizing gender differences in the connectivity between gender and wife beating beliefs when designing interventions. There is a need for efforts to accurately target these values and attitudes to more effectively address gendered attitudes and beliefs about domestic violence in this population.